1970
DOI: 10.1002/pssb.19700400121
|View full text |Cite
|
Sign up to set email alerts
|

An Effective Field Model of the Amorphous Antiferromagnet

Abstract: An effective field model of an amorphous antiferromagnet is developed assuming a distribution of near neighbour distances and hence a distribution of effective field coefficients between interacting atom pairs. It is shown that such a material is characterized by a symmetrical distribution of the total effective field, which, in the absence of any spin correlation, is approximately Gaussian. The model predicts a precise critical or N&l temperature proportional to the square root of the average number of intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

1970
1970
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…The model predicts that below a transition temperature, the Neel temperature TN, the average atomic susceptibility X of a random assembly of magnetic ions coupled by negative exchange interactions is (3) where e, the paramagnetic Neel temperature, is given by (4) and ~ is a known temperature-dependent parameter related to the effective field distribution in the material, and Z and "9 are, respectively, the mean number of neighbors interacting with each ion, and the mean pair effective field coefficient. The susceptibility of the coupled amorphous antiferromagnetic, as given by Eq.…”
Section: Theorymentioning
confidence: 99%
“…The model predicts that below a transition temperature, the Neel temperature TN, the average atomic susceptibility X of a random assembly of magnetic ions coupled by negative exchange interactions is (3) where e, the paramagnetic Neel temperature, is given by (4) and ~ is a known temperature-dependent parameter related to the effective field distribution in the material, and Z and "9 are, respectively, the mean number of neighbors interacting with each ion, and the mean pair effective field coefficient. The susceptibility of the coupled amorphous antiferromagnetic, as given by Eq.…”
Section: Theorymentioning
confidence: 99%
“…In theories of the site percolation problem, it is found that the mean cluster becomes infinitive above a certain critical concentration x c. Long range magnetic ordering does not take place for x < x c where only finite clusters of magnetic ions exist. In this region short range magnetic ordering occurs and the behavior can be analyzed in terms of a duster model [8]. This model could explain, in our case, the rising linewidth and shift of the resonance field in the region ofx < 0.25, as originated from the growth of short-range magnetic correlations.…”
mentioning
confidence: 55%
“…Then, the line narrows with a further increase ofx due to exchange narrowing, with the minimum linewidth corresponding to x ~ 0.03. For larger concentration we observed a single, symmetrical resonance 8 line which broadens monotonically with increasing concentration. The line shope is qualitatively lorentzian characteristic of exchange narrowing.…”
mentioning
confidence: 71%
“…The temperature dependence of the field distribution, however, corresponds to the discussion in (1).…”
mentioning
confidence: 85%